System of estimation of losses of the national economy during the of armed conflict - Kharitonov, Konstantin (Social Development and Security, 2020)
The article describes a system of indicators for carrying out a cost estimation of the economic losses of the state that arise as a result of armed conflict. The analysis of literature shows that today different methods are used to assess the loss to the national economy during an armed conflict, each with its own special system of indicators. A system of indicators that will provide an opportunity to establish a connection between state losses during an armed conflict and economic growth of the state does not take place. The aim of the work is to search for a system of indicators that will solve this problematic issue. The article presents the main components of economic losses, to be exact: direct military expenditures of the country, lost income, which depends on the number of the affected population, additional government expenditures of the government, as well as indirect losses of the state that arose with the onset of armed conflict: displaced capital, emigration of skilled workers and lost educational opportunities for future generations. Taking into account all the components of economic losses that arise as a result of an armed conflict has an impact not only on the total amount of losses, but also on the level of economic development of the state. The application of indicators in the proposed system, on the one hand, establishes the connection between economic development of the state and the components of economic losses caused by armed conflict, and, on the other hand, make it possible to carry out an estimation of these losses. For a more reasonable decision-making on the economic development of our state, the proposed system of indicators estimation the loss to the national economy during the period of armed conflict should be used. For the future the application of such a system will allow establishing the connection between calculated losses and economic growth of the state.